Income Analysis of Seaweed Cultivation with Long Line Method - Asni Asni (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2017)
Seaweed cultivation activities have provided business opportunities to increase income and welfare at family and community level in coastal areas. This is indicated by the number seaweed farmers that continue to increase from year to year. Whereas the livelihood of the community was basically dominated by fishermen, but in fact, nowadays many fishermen are turning the profession into seaweed farmers due to the more promising income and an easy production process of seaweed. This study aimed to determine the costs incurred in seaweed cultivation and income level earned by seaweed farmers. The results of this study were expected to provide additional knowledge and information for the community as well as become a reference for seaweed farmers in improving seaweed cultivation. The study purpose for the government is a recommendation for stakeholders, the private sector, and entrepreneurs in order to develop seaweed cultivation to empower and improve the standard of living of the community. The method of data collection of the study was conducted by observation and questionnaire interview. The results showed that income/profit of seaweed farmers in a raft was Rp. 2.610.000, - with average revenue of Rp 6.232.500 and the average cost of Rp. 3,622,500. Thus cultivation of seaweed in Tanggetada village showed that the R/C ratio of a rift obtained was 1.72, which is greater than 1. It is concluded that seaweed cultivation conducted by farmer respondents in Tanggetada village is worth to be developed.